2010
DOI: 10.1097/bpb.0b013e3283395f5a
|View full text |Cite
|
Sign up to set email alerts
|

Avascular necrosis of distal tibial epiphysis: report of two cases

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Four cases including ours had minor ankle trauma or practiced excessive sport activity; one of them had flexible pes planovalgus [ 2 , 4 , 5 ]. Three cases had neurological abnormalities and one case had congenital abnormality of the tibia without any documented traumatic event [ 3 , 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four cases including ours had minor ankle trauma or practiced excessive sport activity; one of them had flexible pes planovalgus [ 2 , 4 , 5 ]. Three cases had neurological abnormalities and one case had congenital abnormality of the tibia without any documented traumatic event [ 3 , 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first case [ 1 ] had an arthrodesis of the ankle 14 months after injury owing to persistent pain and nonunion of the fracture of the medial malleolus. The second [ 7 ] had congenital sensitive neuropathy and developed destruction of the ankle joint as in Charcot arthropathy; however, clinical and radiological signs found initially may have been early features of Charcot neurogenic joint. The third case [ 5 ] had minor clinical improvement without favorable radiological changes 22 months following injury.…”
Section: Resultsmentioning
confidence: 99%
“…Osteochondrosis of the distal tibial epiphysis is a very uncommon location, with only ten cases reported since 1950 to the best of our knowledge [1,[5][6][7][8][9][10][11]. Bilateral involvement of the distal tibial epiphysis is extremely rare with two case reports in 1993 [6] and 2015 [10].…”
Section: Discussionmentioning
confidence: 99%
“…Three cases were explored with MRI [7][8][9], confirming epiphyseal irregularities and fragmentation with bone edema.…”
Section: Radiographs Show Epiphyseal Flattening and Sclerosismentioning
confidence: 99%
“…Very few case reports have described ON affecting the ankle, and the talus is the more common site of injury than the distal tibia. Two cases of idiopathic AVN of the distal tibial epiphysis were reported by Gasc o et al (21) in a 4-year-old female and an 8-month-old male. In a cohort of 15 childhood cancer survivor patients with corticosteroid-induced ON, Chollet et al (22) found that 67% (20 of 30) of ankles were involved.…”
mentioning
confidence: 87%